2011
DOI: 10.5755/j01.itc.40.4.977
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Three Metaheuristic Approaches for the Maximally Diverse Grouping Problem

Abstract: Given a set of elements and a symmetric matrix representing dissimilarities between them, the maximally diverse grouping problem asks to find a partitioning of the elements into a fixed number of restricted size-groups such that the sum of pairwise dissimilarities between elements in the same group is maximized. We present multistart simulated annealing, hybrid genetic and variable neighborhood search algorithms for solving this problem. We report on computational experiments that compare the performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In order to reach such solutions, the VNS technique for instances of size 2000 required very long computation times. In general, it was discovered from the experiments that all the methods investigated by Palubeckis et al (2011) did not perform very well for large problem instances. The authors have concluded that there remains a lot of room for improvement in the heuristics for solving the MDGP.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…In order to reach such solutions, the VNS technique for instances of size 2000 required very long computation times. In general, it was discovered from the experiments that all the methods investigated by Palubeckis et al (2011) did not perform very well for large problem instances. The authors have concluded that there remains a lot of room for improvement in the heuristics for solving the MDGP.…”
Section: Introductionmentioning
confidence: 94%
“…The current paper is an important extension of our recent work (Palubeckis et al, 2011) on metaheuristics for solving the MDGP. The previous study by Palubeckis et al (2011) has investigated computationally the applicability of three quite different metaheuristics to the MDGP, namely, simulated annealing (SA), HGA and variable neighbourhood search (VNS).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations